A Cognitive Perspective on the Ethical Responsibility of Brain-Computer Fusion - Wang, Yuan; Chen, Feiyu (Journal of Social Science and Humanities, 2026)
At the intersection of neuroscience and artificial intelligence, brain-computer interface (BCI) technology, while enhancing human capabilities, is also reshaping our cognitive world and modes of moral practice. This has increasingly complicated the theoretical study of responsibility. Technology has become a “mediator” in the interaction between humans and the world; consequently, the status and role in action of the brain-computer system, fused with the body, have become ambiguous. It is therefore difficult to determine whether the user remains an “actor” to whom responsibility can be attributed—one who possesses autonomous will and the ability to foresee the consequences of their actions. Grounded in this issue, this paper proceeds from a cognitive perspective, focusing on the fundamental impact of brain-computer fusion on a subject’s moral will and their capacity to foresee the outcomes of their own actions. First, it analyzes the “displacement of moral autonomy” and the “rupture of embodied cognition” caused by technological mediation, examining how the inherently “hetero-creative” (allopoietic) nature of BCIs can alienate the user’s moral judgment of, holistic experience of, and identification with their actions and the resulting consequences. Second, the paper delves into how current technological limitations affect the user’s capacity for foresight. It analyzes the specific processes through which BCIs intervene in the actions of the fused entity via “decoding misalignment” and the “materialization of morality.” Through the theoretical framework of moral materialization, it interprets the value biases embedded within BCI devices during their design phase. Ultimately, by integrating the specific characteristics of BCI technology, this paper dynamically delineates the boundaries of responsibility from the perspective of cognitive capacity, offering a valuable analytical framework for the study of moral responsibility in BCI-mediated actions.